Kontribusi dan Kontroversi Tafsir Orientalis dalam Proses Reformasi Pemikiran Islam Modern - Lulu Nurul Khasanah; Syafiin Mansur (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to analyze the contributions and controversies of Orientalist interpretation in the process of reforming modern Islamic thought, particularly in the Indonesian academic and intellectual context. This study uses library research methods by examining a number of scholarly articles and books discussing the influence of Orientalism on the study of interpretation and hadith. The results show that the Orientalist approach, through historical-critical, philological, and hermeneutical methods, has made a significant contribution to the expansion of a more contextual and rational interpretation methodology. This approach has encouraged the emergence of a new epistemological awareness among Muslim commentators and thinkers in examining sacred texts more scientifically and openly to modern realities. However, this study also uncovered a number of fundamental controversies. Orientalists are often seen as reducing sacred texts to mere historical artifacts and are considered to carry ideological biases and colonial missions that have the potential to shift the authenticity of revelation and local Islamic identity. Thus, the reform of modern Islamic thought ideally does not reject all Orientalist approaches, but rather carries out critical integration while maintaining a balance between scientific methodology and normative faith. The implications of this research emphasize the importance of developing a contextual interpretation of the Nusantara that utilizes the advantages of orientalist methodology without losing the roots of Islamic tradition.